PENINGKATAN KETERAMPILAN BERCERITA SISWA DENGAN MENGGUNAKAN MEDIA POP UP BOOK MATA PELAJARAN BAHASA INDONESIA SISWA KELAS III SD NU AT-THOHIRIYAH GRESIK - Ummatin, Utsna Khoiro (Journal Of Islamic Elementary School (JIES), 2017)
This research is motivated by the low storytelling skills of third grade students of SD NU At-Thohiriyah Gresik in Indonesian lessons. Storytelling in teaching Indonesian is a very important skill because it is closely related to the four language skills. Storytelling according to students is a difficult activity. The low storytelling skills of students have an impact on the low learning outcomes of students. This is due to the monotonous and boring learning atmosphere. To improve the students’ storytelling skills, the authors take action learning by using Pop Up Book media. The formulation of the problem in this study is? (1) How is the use of Pop Up Book media on the storytelling skills of third grade students at SD NU At-Thohiriyah Gresik? (2) How to improve students’ storytelling skills by using Pop Up Book media for class III SD NU At-Thohoriyah Gresik?. This study aims to improve students’ storytelling skills in Indonesian class III subjects at SD NU At-Thohiriyah Gresik by using Pop Up Book media. This type of research is a Classroom Action Research (CAR) which was carried out in 2 cycles and collaborated between Indonesian language teachers and researchers. The CAR model used is the Kurt Lewin model, which in one cycle consists of four stages, including planning, action, observation, and reflection. The subjects in this study were the third grade students of SD NU At-Thohiriyah, totaling 24 students. The data in this study were obtained through observation, interviews, student questionnaires, documentation and non-tests. The results showed that the application of learning storytelling skills using personal experience materials using Pop Up Book media could improve storytelling skills as seen in the increase in student activity, from 69.04 in the first cycle and 78.08 in the second cycle. As well as improving student learning outcomes which can be seen in the increase in the average value of the class during the performance of storytelling skills, namely 65.83 with student learning completeness 41.66% (less) with a total of 10 students completing and 14 students not completing in cycle I and 84.58 with 79.16% (good) student learning completeness with a total of 19 students who completed and 5 students did not complete in the second cycle.